Right and left coronary artery angiography with single Judkins left catheter via right radial artery - Çamcı, Sencer; Ari, Hasan; Arı, Selma; Uğuz, Berat; Özmen, Gökhan; Kınık, Mustafa; Tutuncu, Ahmet; Çavlan, Burcu; Melek, Mehmet; Bozat, Tahsin (The European Research Journal, 2022)
Objectives: The aim of this study was to assess the safety and efficacy of single Judkins left (JL) catheter to view right and left coronary artery in right transradial coronary angiography. Methods: A total of 266 patients underwent coronary angiography from the right radial artery were studied prospectively. Patients with ad-hoc percutaneous coronary intervention (PCI), peripheral angiography, ventriculography or aortography procedures (67 patients) were excluded from the study. Coronary angiography was performed with the JL catheter as single catheter group in 171 of the remaining 199 patients, and with the Judkins right and left catheters as the control group in the other 28 patients. Complications, procedure success, procedure time and fluoroscopy time were evaluated between the two groups. Results: Procedure success were 93% (159/171) in patients with a single catheter group and 96.4% (27/28) in patients with two catheter (Judkins right and left) group (control group) (p = 0.49). Complications (spasm) are the same between the two groups (8 of 171 [4.7%] patients in study group and 1 of 28 [3.6%] patients in control group, p = 0.79). Fluroscopy time in single JL catheter group was significantly higher (6.20 ± 4.97 min vs 3.76 ± 2.78 min, p = 0.01). Conclusions: Single JL catheter using to view right and left coronary artery in right transradial coronary angiography was safe and effective. In our study, the success rate of getting left and right coronary artery images with a single JL catheter as high as 93%. However, insisting on imaging with a single catheter extends the duration of fluoroscopy time.